ENTERPRENEUR MUSLIM: SUATU TINJAUAN - Winbaktianur Winbaktianur; Nur’Aisyiah Yusri (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2020)
The purpose of this paper is to explain Muslim entrepreneurs as one of the factor to increas Indonesia's economic growth. The main challenge facing Indonesia is how to build, develop and improve entrepreneurs. Muslim entrepreneurs are expected to be able to run their businesses based on Islamic concepts al-Quran and hadiths. Muslim entrepreneurs are expected to be able to show their identity as Muslims. As a Muslim entrepreneur, being able to carry out their Islamic values as a human capital in their business activities. The behavior is created by applying four things, namely; fasting, praying, reading the Qur’an and zikir. By applying the dimensions will guide them behavior in each of their business activities, a sense of security in running a business will emerge.